Ultraconserved yet informative for species delimitation: Ultraconserved elements resolve long‐standing systematic enigma in Central European bees. Issue 21 (5th October 2020) - Gueuning, Morgan; Frey, Juerg E.; Praz, Christophe
Abstract: Accurate and testable species hypotheses are essential for measuring, surveying and managing biodiversity. Taxonomists often rely on mitochondrial DNA barcoding to complement morphological species delimitations. Although COI‐barcoding has largely proven successful in assisting identifications for most animal taxa, there are nevertheless numerous cases where mitochondrial barcodes do not reflect species hypotheses. For instance, what is regarded as a single species can be associated with two distinct DNA barcodes, which can point either to cryptic diversity or to within‐species mitochondrial divergences without reproductive isolation. In contrast, two or more species can share barcodes, for instance due to mitochondrial introgression. These intrinsic limitations of DNA barcoding are commonly addressed with nuclear genomic markers, which are expensive, may have low repeatability and often require high‐quality DNA. To overcome these limitations, we examined the use of ultraconserved elements (UCEs) as a quick and robust genomic approach to address such problematic cases of species delimitation in bees. This genomic method was assessed using six different species complexes suspected to harbour cryptic diversity, mitochondrial introgression or mitochondrial paraphyly. The sequencing of UCEs recovered between 686 and 1, 860 homologous nuclear loci and provided explicit species delimitation in all investigated species complexes. These results provide strong evidence for the suitability of UCEs as a fast method for species delimitation even in recently diverged lineages. Furthermore, we provide the first evidence for both mitochondrial introgression among distinct bee species, and mitochondrial paraphyly within a single bee species. Abstract : see also the Perspective by Meng Yuan and John R. Stinchcombe.